The Influence of Institutional Ownership Structure, Capital Structure, and Firm Size on The Stock Exchange Trading Company in Indonesia (BEI) - Santoso, Eko Budi; Fathoni, Ahmad Fauzan; ', Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to examine the effects of institutional ownership, capital structure, and firm size on firm value in trading company in jakarta stock exchange for 2009 until 2012. Purposive sampling method is used to get our sampling form thirty firm population, we acquired twenty companies. For the analyse our data, we used multiple regresion analyse. Testing while t-test, f-test and coefficient determinasi (R2) are used to examine our hypotesis. The result that capital structure variable negative and significantly on firm value. moreover firm size effect positively and significantly on firm value. whereas, institutional ownership has no effect on firm value.Keywords: Enterprise Value, Institutional Ownership, Capital Structure and Firm Size.